Effect of tillage packages and herbicides on energy and economics of wheat in transplanted rice (Oryza sativa)wheat (Triticum aestivum) system* - JAIN, NAMRATA; JAIN, VINAMARTA; MISHRA, J S; KEWAT, M L (The Indian Journal of Agricultural Sciences, 2011)
Rice ( O y a sativa L.) - wheat (Triticum aestivum L. emend. Fiori & Paol.) cropping system is one of the most common and widely adopted cropping systems under irrigated conditions. Conventional tillage practices followed by farmers after transplanted rice involves high use of machines, labour and energy as it is done to change the low permeability soil sfzucture created for rice to well aerated structure for wheat (Sharma et al. 2002).....